Structure and activation of the Drosophila insulin receptor by three Drosophila insulin-like peptides. - Cai, K.; Ng, M.; Yamamoto, R.R.; Hossain, M.A.; Hall, C.; Wade, J.D.; Tatar, M.; Choi, E.; Bai, X.C. (Nature communications, 2025)
Insulin/IGF signaling (IIS) is a highly conserved pathway essential for physiological regulation from yeast to mammals. In Drosophila melanogaster, a single insulin-like receptor (dmIR) interacts with various insulin-like peptides (DILPs), leading to diverse signaling and functional outcomes. However, the mechanisms by which different DILPs result in varied receptor activation and biological responses remain unclear. Here, we determine the cryo-electron microscopy (cryo-EM) structures of dmIR in complex with three DILPs: DILP1, DILP2, and DILP5. Our structural analyses reveal that each DILP induces distinct conformations of dmIR: the dmIR/DILP5 complex adopts the ?-shaped asymmetric conformation with three bound DILP5 molecules; the dmIR/DILP2 complex displays the ?-shaped asymmetric conformation with a single bound DILP2 molecule; and the dmIR/DILP1 complex shows both a ?-shaped asymmetric conformation and a symmetric conformation that resembles a T-shape with a splayed stem. Functional assays demonstrate that the efficacy of DILP-mediated dmIR activation differs, with DILP5 inducing higher levels of receptor autophosphorylation, followed by DILP2 and DILP1. Together, these findings suggest that the distinct interactions between dmIR and DILPs dictate specific patterns of receptor activation.